2001
DOI: 10.1007/s001250100581
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine-induced inhibition of nitric oxide production in platelets: a study on healthy and diabetic subjects

Abstract: Moderate increases in the plasma concentrations of homocysteine are associated with an increased incidence of arteriosclerosis and cardiovascular disease [1]. Homocysteine could exert adverse vascular effects by a number of mechanisms: production of reactive oxygen species caused by auto-oxidation, reduced endothelial generation of nitric oxide (NO) and/or enhancement of vascular smooth muscle cell proliferation [2]. Recent data have shown that flowmediated vasodilation is reduced in the presence of methion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…Results from experimental studies which showed that hyperhomocysteinaemia interferes with the vasodilator and antithrombotic function of nitric oxide [29,30] and with the peroxide-mediated effects on arterial prostacyclin synthesis [31] were supported by clinical findings. Recently, an inverse relation between a range of tHcy concentrations and endothelium-dependent coronary blood flow was documented [32].…”
Section: Discussionmentioning
confidence: 85%
“…Results from experimental studies which showed that hyperhomocysteinaemia interferes with the vasodilator and antithrombotic function of nitric oxide [29,30] and with the peroxide-mediated effects on arterial prostacyclin synthesis [31] were supported by clinical findings. Recently, an inverse relation between a range of tHcy concentrations and endothelium-dependent coronary blood flow was documented [32].…”
Section: Discussionmentioning
confidence: 85%
“…However, NO production in platelets from diabetic patients was lower than that in nondiabetic patients. 47 Thus, no consistent pattern regarding the relationship between homocysteine and NO availability/vascular tone emerges from studies performed to date.…”
Section: Pathophysiological Considerationsmentioning
confidence: 96%
“…40 Whether the factors discussed in aggregate lead to differences in plasma homocysteine level between patients with diabetes and healthy subjects is unclear. Some authors have reported higher homocysteine levels in diabetic patients, 15,16,[41][42][43][44][45][46] while others have found similar 14,45,[47][48][49][50] or even lower levels. 35,[51][52][53][54][55][56] These discrepancies may be due mainly to the fact that most studies did not account for folate status and renal function, the two most important determinants of plasma homocysteine level.…”
Section: Determinants Of Plasma Homocysteine Concentrationmentioning
confidence: 99%
“…It has been reported that hyperhomocysteinemia may also be associated with the incidence of ischemic brain stroke (Refsum et al, 1998), mainly due to pleiotropic activity of homocysteine and acceleration of atherosclerotic changes (Refsum et al, 1998;Thambyrajah et al, 2000). In fact, Hcy suppresses NO production by endothelial cells (Upchurch et al, 1997) and platelets (Mutus et al, 2001) and increases generation of reactive oxygen species (ROS) by the release of arachidonic acid from platelets (Signorello et al 2002). It also inhibits glutathione peroxidase (Upchurch et al, 1997), and thus stimulates proliferation of endothelial cells (Jeremy et al, 1999;Domagala et al, 1998).…”
Section: Effect Of Hyperhomocysteinemia On Spca Expressionmentioning
confidence: 99%